PENGUATAN DIMENSI PROFIL PELAJAR PANCASILA BERIMAN, BERTAKWA KEPADA TUHAN YANG MAHA ESA DAN BERAKHLAK MULIA MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA - Lestari, Yunita Dewi; Jamaludin, Ujang; Damanhuri, Damanhuri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to describe the process, supporting factors and inhibiting factors in the implementation of strengthening the Pancasila Student Profile dimensions of faith, devotion to God Almighty, and students' noble morals through learning Pancasila education. The research method used is a qualitative descriptive method. The data analysis technique used is the Miles and Huberman model data analysis technique which consists of data collection, data reduction, data presentation and conclusions. The research results show that the process of strengthening the Pancasila Student Profile dimensions of faith, devotion to God Almighty, and noble character is integrated through Pancasila learning activities in preliminary activities, core activities and closing activities, apart from that the strengthening process is also carried out through habituation activities and school programs. The supporting factors in the process of strengthening the character of the Pancasila Student Profile at SDN Periuk 1 include the readiness of teachers to carry out learning that is integrated with strengthening the Pancasila Student Profile, the availability of school facilities and infrastructure, and the participation of parents and the surrounding community in organizing activities at school. Meanwhile, the inhibiting factors faced are inhibiting factors from outside the school which originate from students' social interactions which are less supervised by parents.